Rare phenotypes in domestic animals: unique resources for multiple applications. (14th December 2015) - Leroy, G.; Besbes, B.; Boettcher, P.; Hoffmann, I.; Capitan, A.; Baumung, R.
Summary: Preservation of specific and inheritable phenotypes of current or potential future importance is one of the main purposes of conservation of animal genetic resources. In this review, we investigate the issues behind the characterisation, utilisation and conservation of rare phenotypes, considering their multiple paths of relevance, variable levels of complexity and mode of inheritance. Accurately assessing the rarity of a given phenotype, especially a complex one, is not a simple task, because it requires the phenotypic and genetic characterisation of a large number of animals and populations and remains dependent of the scale of the study. Once characterised, specific phenotypes may contribute to various purposes (adaptedness, production, biological model, aesthetics, etc.) with adequate introgression programmes, which justifies the consideration of (real or potential) existence of such characteristics in in situ or ex situ conservation strategies. Recent biotechnological developments (genomic and genetic engineering) will undoubtedly bring important changes to the way phenotypes are characterised, introgressed and managed.